2016
DOI: 10.1111/den.12626
|View full text |Cite
|
Sign up to set email alerts
|

Self‐expanding metal stents for acute refractory esophageal variceal bleeding: A systematic review and meta‐analysis

Abstract: Objectives Esophageal variceal bleeding is a severe complication of portal hypertension with significant morbidity and mortality. A substantial portion of cirrhotics fail to respond to conventional medical therapy and band ligation, necessitating alternative treatments including SEMS placement for acute refractory esophageal variceal bleeding. To perform a systematic review and structured meta-analysis of all eligible studies to evaluate the technically feasibility, safety, clinical efficacy, and survival adva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 35 publications
0
30
0
Order By: Relevance
“…A recent metaanalyses of 12 studies comprising a total of 155 patients reported a promising clinical success rate of 96% within 24 hours using SEMS for refractory variceal bleeding. 29 However, in three of the included studies, haemostasis within 24 hours was only achieved with lower rate ranging from 78% to 89%. 23,30,31 Another metaanalyses comprising n = 134 showed failure-to-control bleeding rate of 14.2%.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…A recent metaanalyses of 12 studies comprising a total of 155 patients reported a promising clinical success rate of 96% within 24 hours using SEMS for refractory variceal bleeding. 29 However, in three of the included studies, haemostasis within 24 hours was only achieved with lower rate ranging from 78% to 89%. 23,30,31 Another metaanalyses comprising n = 134 showed failure-to-control bleeding rate of 14.2%.…”
Section: Discussionmentioning
confidence: 93%
“…We found a high percentage of successful bleeding control within five days (82.4%) and one‐third had successful bleeding control without bleeding events during follow‐up. A recent meta‐analyses of 12 studies comprising a total of 155 patients reported a promising clinical success rate of 96% within 24 hours using SEMS for refractory variceal bleeding . However, in three of the included studies, haemostasis within 24 hours was only achieved with lower rate ranging from 78% to 89% .…”
Section: Discussionmentioning
confidence: 99%
“…Failure to control acute bleeding and very early rebleeding were assessed by two experienced clinicians. Patients with failure of initial hemostasis or very early rebleeding were treated with a vasoconstrictor along with balloon tamponade, SX‐ELLA‐Danis stent or transjugular intrahepatic portosystemic shunt (TIPSS) as clinically indicated. Delayed rebleeding was defined as when the criteria for failure to control acute variceal bleeding occurred between 5 and 30 days after enrolment in patients achieving control of acute bleeding.…”
Section: Methodsmentioning
confidence: 99%
“…Balloon tamponade with a Sengstaken-Blakemore or a Linton-Nachlas tube may still be used in the very rare case of massive exsanguinating bleeding or recurrent bleeding as a "bridge" to TIPS or another definitive treatment. However, oesophageal self-expandable metallic stents have been shown to be very effective 49 and a recent RCT showed that oesophageal stents are as effective but safer than balloon tamponade. 50 This is part of current recommendations.…”
Section: Oesophageal Tamponadementioning
confidence: 99%